THE URBAN PLANNING CONCEPT BASED ON SMART CITY APPROACH - Muhammad Bakri; Anita Ahmad Kasim (International Journal on Livable Space, 2018)
Smart City comes as a strategy to reduce the problem due to rapid urban growth and urbanization. The concept of Smart City is needed to ensure the conditions of a habitable City in the context of rapidly growing urban population growth. The urgency of this challenge prompted many cities to begin to find smarter ways of managing urban areas. One way to make the concept of the smart city is to make the city an icon that is sustainable and livable. This study aims to provide the necessary information in building and developing a city through the smart city approach. This paper clarifies the meaning of the word "smart" in the city context through an approach based on an in-depth literature review of the relevant study. This study will identify the main factors and characteristics that characterize smart cities. The method used to obtain various factors and the characteristics of the Smart City in the arrangement of a region is done by studying various kinds of the literature of various concepts and components in the Smart City. The results obtained in this study there is a concept of Smart City in urban planning by mapping various factors and characteristics in the Smart City. Keywords: Smart City, Urban planning, smart city characteristic